1001 ways to reward employees - Nelson, Bob, 1956- (HighBridge Audio, 2009)
Why is 1001 ways to reward employees, with over 1.4 million copies in print, such an extraordinary bestseller? Because a little over ten years ago Bob Nelson took the seeds of an idea and turned it into something indispensable for business. The idea? That it's not a raise that motivates an employee, and it's not a promotion--what really sparks a person to perform are those intangible, unexpected gestures that signify real appreciation for a job well done. Now, after having worked with thousands of organizations in the years since 1001 ways to reward ... was first published, Bob Nelson presents a second edition packed with hundreds of new ideas and examples of how companies are using rewards and recognitions to boost productivity and keep their valued employees happy. Airplane mechanics are rewarded with balloons and pinwheels. Another manager calls his employees' mothers and thanks them for raising such industrious children.